Incidencia Del Contrabando Y La Subfacturación En El Mercado De Refacciones Automotrices En Bogotá D.C., Colombia. (2024)
Smuggling is commonly associated as a policy-related phenomenon. tariffs of a country, since it directly or indirectly affects the increase or decrease of the same. But it is only one more variable of this crime because factors such as the economic openness of a country, the socioeconomic and sociocultural conditions, the fragile judicial system and corruption It also allows it to happen. Likewise, smuggling can occur in two ways, the first is through open contraband since it is the simplest way to carry out this practice, it can be defined as the way to introduce goods into the country without being declared. They are generally goods that come without registration from the country of origin or a third country is used as something temporary which creates great difficulty in being able to detect it or be able to quantify it. The second is the technical contraband which occurs when the markings are declared by their position tariff, which can be used to declare them for a different value, for evasion of a tax, the application of preferential treatment or an import modality that does not corresponds to the merchandise.